A picture of radiography education across Europe. Issue 1 (February 2016) - McNulty, J.P.; Rainford, L.; Bezzina, P.; Henner, A.; Kukkes, T.; Pronk-Larive, D.; Vandulek, C.
Abstract: Purpose: To establish an understanding of radiography education across Europe by surveying higher education institutions registered as affiliate members of the European Federation of Radiography Societies (EFRS). Method: An online survey was developed to ascertain data on: curricula, duration, credit load, accreditation requirements, staff qualifications, staff and student exchange opportunities, and availability of postgraduate programmes. Responses were identifiable in terms of educational institution and country. All 46 affiliated educational institutions were invited to participate in the survey. Descriptive and thematic analyses are reported. Results: A response rate of 89.1% (n = 41) was achieved from educational institutions representing 21 countries. The majority of institutions (63.4%) offer a combined Medical Imaging, Radiotherapy and Nuclear Medicine programme; dedicated Medical Imaging programmes are offered by 14 institutions (34.2%); dedicated Radiotherapy programme by one institution (2.4%), and a dedicated Nuclear Medicine programme by only three institutions (6.5%). The Bologna (Bachelor) cycle has been adopted by 90.2% of responding institutions. The majority of institutions (53.7%) indicated programmes of 3 years in duration, others stated 3.5–4 years. Only 14.6% of institutions require 'International Level' accreditation for the Bachelors radiography programme. Postgraduate programmes were not offered by 26.8% of institutions and a deficit in Doctoral status for radiography educators was identified. Conclusions: The Bologna (Bachelor) cycle for radiography education has been adopted across the majority of institutions, however, full alignment remains a priority. Postgraduate radiography education opportunities across Europe appear to be insufficient and further investigation of radiography accreditation processes is justified to ensure harmonisation of practice. Highlights: The majority of institutions are compliant with the Bologna process and the ECTS. Programme variability presents an ongoing challenge in recognising qualifications. A European accreditation system may improve radiography education quality standards. The very limited availability of Doctoral programmes is evident.